Proteomic approach to identify KLF1-regulated factors in Erythroid Island-like macrophages and their role in the maturation of red blood cells in vitro - da Cruz Ventura, Telma Filipa (The University of Edinburgh, 2023)
Blood cell transfusion is used routinely in the clinic to treat acute red blood cell (RBC) loss and disease. Limitations in donor supply has led to attempts to generate RBCs in vitro from alternative sources but it has proven really challenging to generate fully mature enucleated RBCs in sufficient quantities. In the mammalian adult, including humans, maturing erythroid cells proliferate and differentiate within a specified niche known as the erythroblastic island (EBI). These islands are formed by a central macrophage that is surrounded by maturing erythroid cells. Their close proximity and signalling exchange lead to the production of fully mature red blood cells prior entering circulation. Krueppel-like factor 1 (KLF1) is a key regulator transcription factor present in both erythroid cells and in macrophages within the EBI niche. Using genetic engineering techniques, our lab generated a human induced pluripotent stem cell (hiPSC) cell line where KLF1 could be activated by tamoxifen addition. Macrophages generated from this cell line demonstrated good support for the maturation of erythroid cells in vitro, thus launching a tool for the study of the signalling interface occurring between macrophages and erythroid cells within the EBI niche. In this project the phenotype of hiPSCs macrophages was characterised upon the addition of different concentration of tamoxifen, to optimise the activation of KLF1 in these cells. To further understand the signalling provided by KLF1 activated macrophages within the EBI niche, a quantitative proteomic analysis was carried out. Gene ontology (GO) analysis showed that the majority of KLF1 upregulated proteins are protein-binding proteins, that can be found in the cell membrane and vesicle associated proteins. The role of macrophage-derived extracellular vesicles on the differentiation and maturation of umbilical cord CD34+ haematopoietic progenitors into erythroid cells was then investigated. Depletion of these vesicles from macrophage conditioned media, resulted in a reduction in erythroid progenitor viability of erythroid progenitors in vitro and a reduction in the proportion of fully mature cells. This suggests that extracellular vesicles play a supportive role in the maintenance of the integrity of the progenitor cells in vitro, as well as for their differentiation to erythrocytes in later stages of the process. I demonstrated that KLF1 is unlikely to play a direct role in the production of vesicles associated with cell integrity and maturation of erythroid cells, since their production and functional effects were independent of KLF1 activation. Following analysis of the proteomic scanning led to the selection of three upregulated membrane proteins (Transferrin receptor – TFRC- Lectin, mannose binding 1 protein - LAMN1 - and Lysosomal Associated Membrane Protein 2 - LAMP2) that were subsequently synthesised and their potential for the support of erythroid cell maturation and differentiation in vitro was assessed. In the presence of the ectodomain of the selected peptides there was an increase of erythroid cells expressing CD235a in culture, but enucleation was not affected in most of the conditions. Pathway analyses of the proteomic data showed that KLF1-activated macrophages are highly metabolic, where most of the upregulated proteins are found to be part of TCA cycle, pyruvate metabolism and ATP synthesis. Taken together this study has generated a proteomic dataset opening new insights for the study of the role of macrophages within the EBI niche. It also demonstrated a functional role for extracellular vesicles in the differentiation and maturation of red blood cells in vitro. Further studies in these areas will aid in the production of RBC in vitro for use in disease modelling and cell therapy.
A proteomic approach to identify KLF1-regulated factors in Erythroid Island-like macrophages and their role in the maturation of red blood cells in vitro
Keywords: KLF1-regulated factors; Erythroid Island-like macrophages; red blood cells in vitro; Blood cell transfusion; acute red blood cell (RBC) loss; acute red blood cell (RBC) disease; enucleated RBCs; fully mature enucleated RBCs; erythroblastic island (EBI); maturing erythroid cells; Krueppel-like factor 1 (KLF1); regulator transcription factor; human induced pluripotent stem cell (hiPSC); tamoxifen; KLF1 upregulated proteins; protein-binding proteins; macrophage-derived extracellular vesicles; umbilical cord CD34+ haematopoietic progenitors; erythroid cells; erythroid cells expressing CD235a; extracellular vesicles